THE EVAL UA TION OF EFFECTIVENESS OF RHIZOBIUM LEG UMINOSAR UM STRAINS IN DIFFERENT HOST PLANTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Pot experiments were carried out to investigate the effectiveness of six Rhizobium leguminosarum strains stored at the collection of Latvia University of Agriculture. Three of them are included at international Rhizobium data base. The obtained results showed that all Rhizobium strains were active and inoculated plants formed nodules on the roots. Inoculation with Rhizobium strains increased the proportion between shoots and root weight. The dry matter content of inoculated plants increased in comparison with untreated ones. The negative correlation between the plant weight and nitrogen content in the dry mater of shoots was observed. The host plant specificity was observed for tested Rhizobium leguminosarum strains.